PENYULUHAN DAN PELATIHAN PEMBUATAN SABUN PADAT ORGANIK DI DESA PEGUYANGAN DENPASAR - Gusti Ayu Dewi Lestari (Universitas Lancang Kuning, 2021)
Teenagers in Peguyangan Kangin Village, Denpasar, Bali still do not understand the process of making organic solid soap because they have never received training on making organic solid soap. The aim of community service is to provide counseling and training in the manufacture of organic solid soap made from raw materials coconut oil, palm oil and olive oil. Pretest and posttest were carried out before and after the activity which is one form of evaluation of this activity. The result of the activity showed that counseling and training on making organic solid soap had provided information and knowledge to the youth of Peguyangan Kangin Village and could have been carried out well by the participants.